Republic of Kazakhstan : Accounting and Auditing - World Bank (Washington, DC, 2012)
This report on the report on the observance of standards and codes (ROSC) in Kazakhstan provides an assessment of accounting, financial reporting, and auditing requirements and practices within the enterprise and financial sectors in Kazakhstan. The report uses International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA), and draws on international experience and good practices in the field of accounting and audit regulation, including in European Union (EU) Member States, to assess the framework for financial reporting and to make policy recommendations. The policy recommendations aim to help the Kazakhstan Government to support the country's integration into the global economy, in particular through strengthening the corporate sector's accounting, financial reporting and auditing practices. The financial sector, which is dominated by private commercial banks, has been one of the fastest growing sectors in Kazakhstan. However, while lending to the private sector has increased, credit risk analysis remains underdeveloped and there are problems with assessing the underlying portfolios owing to a significant lack of transparency regarding related parties and ultimate economic beneficiaries. The role of the non-banking financial sector is still limited but growing. This report shows much remains to be done if Kazakhstan wishes to raise the quality of accounting and auditing practices to a level in line with more-developed economies.